1984
DOI: 10.1210/jcem-59-5-899
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Somatomedin-Binding Protein from Preterm Amniotic Fluid. Development of a Radioimmunoassay*

Abstract: Amniotic fluid binding protein (AFBP) is a heat and acid stable somatomedin (Sm)-binding protein with a mol wt of 35-40,000 and an isoelectric point of +/- 4.7. It is reactive in RRAs for Sm and inhibits Sm activity in Sm bioassays. AFBP was purified from midgestational human amniotic fluid (AF) using acid-ethanol extraction, Sephadex G-150 chromatography, high speed gel filtration chromatography, and disc gel-electrophoresis. Specific binding activity (microgram equivalents per mg protein) was quantitated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
1

Year Published

1988
1988
1999
1999

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(47 citation statements)
references
References 84 publications
1
44
1
1
Order By: Relevance
“…Our IGF-BP25 RIA is similar to that developed in other laboratories, and we have found that levels in normal nonfasting children and adults (Lee PDK, Powell DR, unpublished data) are comparable to levels reported by others (22,24,25), IGF-BP25 levels for large groups of fasting children have not been published. To avoid the reported diurnal variation of circulating IGF-BP25 levels (25), all samples used in the study and control populations were collected in the morning after an overnight fast.…”
Section: Discussionsupporting
confidence: 79%
“…Our IGF-BP25 RIA is similar to that developed in other laboratories, and we have found that levels in normal nonfasting children and adults (Lee PDK, Powell DR, unpublished data) are comparable to levels reported by others (22,24,25), IGF-BP25 levels for large groups of fasting children have not been published. To avoid the reported diurnal variation of circulating IGF-BP25 levels (25), all samples used in the study and control populations were collected in the morning after an overnight fast.…”
Section: Discussionsupporting
confidence: 79%
“…Assuming that amniotic fluid IGF-I is of fetal origin, then the lack of responsiveness of IGF-I to acute maternal substrate deprivation may reflect a pool that is slowly responsive to acute perturbations of fetal nutritional status. Alternatively, it may be that G-50 acid chromatography does not adequately separate IGF-I from the amniotic fluid binding protein, and thus does not accurately reflect the state of IGF-I in the amniotic fluid compartment under conditions of suboptimal nutrition (20,21).…”
Section: Resultsmentioning
confidence: 99%
“…wt IGF-BP isolated from human amniotic fluid was raised and purified as described previously (Drop et al, 1984a). The antibody preparation was depleted for Escherichia coli and Xgtl 1 proteins and by incubation with nitrocellulose filters that had been lifted from confluent lysis plates of E.coli Y1090/Xgtl 1, induced with10 mM isopropyl,B-d-thiogalactopyranoside (IPTG).…”
Section: Methodsmentioning
confidence: 99%
“…wt IGF-BP by proteolytic processing . The NH2-terminal amino acids of the 30-35-kd BPs derived from amniotic fluid, human serum and the HEPG2 cell line are completely homologous, suggesting that these proteins are in fact identical (Drop et al, 1984a;Povoa et al, 1985). Recently, another 35-kd IGF-BP has been isolated from soluble extracts of term human placental/fetal membranes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation